Microfluidic devices for biomedical applications - Li, Xiujun James; Zhou, Yu.; ScienceDirect eBooks (Cambridge, UK : Woodhead Pub. Ltd., 2013)
Microfluidics or lab-on-a-chip (LOC) is an important technology suitable for numerous applications from drug delivery to tissue engineering. Microfluidic devices for biomedical applications discusses the fundamentals of microfluidics and explores in detail a wide range of medical applications. The first part of the book reviews the fundamentals of microfluidic technologies for biomedical applications with chapters focussing on the materials and methods for microfabrication, microfluidic actuation mechanisms and digital microfluidic technologies. Chapters in part two examine applications in drug discovery and controlled-delivery including micro needles. Part three considers applications of microfluidic devices in cellular analysis and manipulation, tissue engineering and their role in developing tissue scaffolds and stem cell engineering. The final part of the book covers the applications of microfluidic devices in diagnostic sensing, including genetic analysis, low-cost bioassays, viral detection, and radio chemical synthesis. Microfluidic devices for biomedical applications is an essential reference for medical device manufacturers, scientists and researchers concerned with microfluidics in the field of biomedical applications and life-science industries. Discusses the fundamentals of microfluidics or lab-on-a-chip (LOC) and explores in detail a wide range of medical applicationsConsiders materials and methods for microfabrication, microfluidic actuation mechanisms and digital microfluidic technologiesConsiders applications of microfluidic devices in cellular analysis and manipulation, tissue engineering and their role in developing tissue scaffolds and stem cell engineering.
8.3 Microscale fluid dynamics8.4 Manipulation technologies; 8.5 Manipulation of cancer cells in microfluidic systems; 8.6 Conclusion and future trends; 8.7 Sources of further information and advice; 8.8 References; 9 Microfluidic devices for single-cell trapping and automated micro-robotic injection; 9.1 Introduction; 9.2 Device design and microfabrication; 9.3 Experimental results and discussion; 9.4 Conclusion; 9.5 Acknowledgements; 9.6 References; 10 Microfluidic devices for developing tissue scaffolds; 10.1 Introduction.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Microfluidic devices; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Microfluidic devices; Electronic books